Analysis of the impact of external optical feedback on the performance of high-power and high-brightness laser diodes - Helal, Mohamad Anas (2017)
The main motivation behind this work was to answer the following question: what is the impact of unintentional external optical feedback on laser performance. During the course of this PhD, however, two more questions were raised: how does the spectral external feedback (i.e. intentional feedback from a grating) enhances the spectral performance of the laser? And why does the beam quality of Distributed Bragg Reflector (DBR) tapered lasers degrade at >2.5 times the threshold current? To answer these two questions, new simulations were performed and more results were obtained. The impact of external feedback can be positive or negative. High-brightness lasers are mostly characterised under stand-alone conditions. Nevertheless, high-brightness lasers are almost always operated in external cavity configurations. The external cavity will produce reflections, whether they are intentional reflections off mirrors or gratings, or unintentional reflections off the optics elements. In order to have an accurate prediction of how the high-brightness laser will perform in an external optical system, a modelling tool, which is capable of self-consistently modelling the laser cavity and the fields propagating in the external optical system, is needed. In this work, an external cavity laser simulation tool was developed. This tool consists of an in-house 2.5D laser modelling tool, Speclase; a commercial coherent ray-tracing software, OpticStudio; and an interface software to bidirectionally couple the two different light modelling algorithms used by these tools: finite difference beam propagation (FD-BPM) method and coherent ray-tracing. The author was responsible for: developing the interface software – using Matlab - between Speclase and OpticStudio. Also, the author cooperated with Dr. Kaunga-Nyirenda to modify Speclase so that the coupling between Speclase and OpticStudio modelled the physics correctly. This way the software was able to produce external cavity designs to study the impact of external feedback, intentional and unintentional. The external cavity tool was used to investigate and analyse the impact of parasitic reflections on the performance of high-brightness diode lasers. It was also used to analyse how the Littrow cavity works, which is an example of how intentional feedback is used to improve laser performance. Finally, Speclase was used to investigate why the beam quality of high-brightness DBR tapered lasers degrade at higher power, i.e. at currents > 2.5 times the threshold current. This gave an insight on how the external optical feedback affects the degradation of beam quality. It also helped differentiate between the impact of external feedback coupled to the fundamental mode and to the higher-order vertical modes. This work contributes to the knowledge of how external feedback alters the performance of high-brightness laser diodes. It shows that unintentional feedback can lead to the degradation of output power, power conversion efficiency and beam quality. It also shows the significance of modal discrimination and external cavity coupling coefficients and how they can be used to mitigate the unwanted impacts of external optical feedback. The developed model also contributes to the optimisation of external cavity systems with intentional feedback to get optimum performance. It shows how spectral feedback coupled to the laser cavity can force the laser to favour a specific wavelength that is, by allowing the beam of that wavelength to couple into the RW section, while other wavelengths are spatially filtered out. This work also answers a significant question of why the beam quality of DBR tapered lasers degrade at currents 2.5 times the threshold current, although the back- facet reflectivity is patterned, allowing fields propagating outside the RW to escape the structure. The results show clearly how the patterned back facet reflectivity creates a diffraction of the back-propagating beam which allows the diffracted beam to exit the RW and couple into the taper section, exciting higher-order lateral modes.